Diamond films and coatings development, properties, and applications - Davis, Robert F. 1942- (Noyes Pub., 1993)
Reviews diamond films and coatings covering their properties, growth, deposition, characterization, and applications.
Keywords: Diamond thin films.; Diamonds, Artificial.; elektronické knihy; electronic books